Pertanggung Jawaban Pelaku Usaha atas Pelanggaran Hak Cipta oleh Perusahaan Mie Gacoan di Bali - Windi Anggraeni; Syira Ramadani (Lembaga Pengembangan Kinerja Dosen, 2025)
In Indonesia, copyright infringement in the music sector continues to be a significant issue, particularly when musical works are commercially exploited by businesses. This study examines the accountability of businesses towards music royalty payments through a case study of Mie Gacoan and the Collective Management Institute (LMK) SELMI. The research method used is normative juridical with additional research data collected through literature review, including related regulations and various previous studies on music copyright protection. The results of the study confirm that businesses are obliged to pay royalties for the use of copyrighted works, as stipulated in Law Number 28 of 2014 and Government Regulation Number 56 of 2021 concerning Song/Music Royalty Management. The dispute between Mie Gacoan and LMK SELMI demonstrates the weak awareness of businesses regarding legal obligations and highlights the importance of the LMK's role in ensuring the fulfillment of creators' economic rights. This study emphasizes that legal certainty, the level of public awareness of the law, and consistency in law enforcement are important factors in realizing copyright protection in Indonesia.